Stochastic renewable energy resources integrated multi-objective optimal power flow - Sundaram B. Pandya; Hitesh R. Jariwala (Universitas Ahmad Dahlan, 2020)
The modern state of electrical system consists the conventional generating units along with the sources of renewable energy. The proposed article recommends a method for the solution of single and multi-objective optimal power flow, integrating wind and solar output energy with traditional coal-based generating stations. In the first part of the article, the two wind power plants and one solar PV power plants are incorporated with the thermal power plants. The optimal power flow problem of single and conflicting multi-objectives are taken with this scenario. The second part of the paper, solar power plant is replaced with another wind power plant with the conventional coal-based power plants. The techno-economic analysis are done with this state of electrical system. In proposed work, lognormal and weibull probability distribution functions are also utilized for predicting solar and wind outputs, respectively. A non-dominated multi-objective moth flame optimization technique is used for the optimization issue. The fuzzy decision-making approach is applied for extracting the best compromise solution. The results are validated though adapted IEEE-30 bus test system, which is incorporated with wind and solar generating plants.